Panji Ecovillage Homestay: the implementation of Community Based Tourism - Nyoman Dini Andiani; Ni Ketut Arismayanti; Earlike Fitria Anwar Sani; Ni Made Mas Yogiswari (Jurnal Pariwisata Pesona, 2024)
Ecovillage is a current trend because through this concept it is hoped that people in tourist villages in particular will have a culture that cares about the environment, especially being wiser in using plastic waste. This study was conducted to determine community involvement in the development of ecovillage homestays in the Panji tourist village. Through in-depth interview techniques and observations with the owners of houses used as homestays and other community components, and supported by community-based tourism theory, it was found that the development of homestay ecovillages must start from the top down to make the community aware that the potential of each house is very unique and interesting for used as a homestay. The findings show that through the development of homestays, people become aware of the importance of environmental cleanliness and the main actor that becomes the attractiveness of the homestay itself is the activities of the homeowner. The implication of this study is that the development of homestays with the ecovillage homestay concept has been able to involve the community in creating tourist attractions, as well as educating homeowners and visiting tourists to be able to maintain culture and preserve environmental sustainability in Panji Village.